Organizational cultural identification and employee engagement: Rethinking organizational performance in creative enterprises - Liu, Yangtong; Hussain, Ibiwani Alisa Binti (Edelweiss Applied Science and Technology, 2025)
In the context of the experience economy, cultural and creative enterprises have increasingly become key platforms for the dissemination of social values. Their operations rely heavily on employees’ identification with organizational culture and their intrinsic motivation. This study is structured around the conceptual link among organizational cultural identification, employee engagement, and organizational performance. Based on a comprehensive review of existing literature and theoretical integration, it explores the mechanisms through which employee engagement is generated and its influence on organizational performance in cultural and creative enterprises. The findings suggest that the behavioral expression of engagement is rooted in employees’ cognitive assimilation and emotional identification with organizational culture. Through pathways such as brand co-creation, innovation activation, and organizational collaboration, employee engagement contributes significantly to the enhancement of non-financial performance. Drawing on the characteristics of cultural and creative organizations, this paper proposes management recommendations such as reshaping the performance evaluation system, aiming to provide both theoretical insight and practical guidance for the sustainable development of culture-oriented enterprises.